Flaubert and the retranslation of Madame Bovary - Sharon Deane (Flaubert: Revue Critique et Génétique)
Of all Flaubert’s works, Madame Bovary holds the accolade of being subject to the highest frequency of retranslation in the British literary system. A survey of these diverse retranslations affords an insight into when and how the versions arose amidst varying socio-cultural and economic configurations. This historical approach sheds new light on previous assumptions regarding the role of retranslation: rather than following a straightforward path from defective initial translation to accomplished recent retranslation, a more complex picture emerges. With Madame Bovary we can see how the boundaries of retranslation become blurred, and can identify evidence of regression, struggles for differentiation, as well as the collective significance of this corpus.